2013
DOI: 10.4236/ajcc.2013.24026
|View full text |Cite
|
Sign up to set email alerts
|

Lightning Enhancement in the Amazon Region Due to Urban Activity

Abstract: Urbanization has an increasing contribution to anthropogenic climate forcing. The impact arises mainly from the Urban Heat Island (UHI) effect and aerosol anthropogenic emissions. An important but not completely understood consequence of this forcing is its effect on local lightning activity. Changes in lightning activity may result in a feedback on the climate system. In this article, it investigates changes in the lightning activity in the city of Manaus, located in the Amazon region of Brazil. It is found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
5
0
2
Order By: Relevance
“…Our findings are in line with previous works that identified temperature as the main factor defining maize performance in the context of global change, with a prevalence of declines in yields (Bassu et al, 2014;Rose et al, 2016;Tao & Zhang, 2011). They are also consistent with recent modeling and meta-analysis reports, which observed a greater sensitivity to rising temperatures in maize than in soybean (Justino et al, 2013;Rose et al, 2016;Zhao et al, 2017). Previous reports from both CO 2 enrichment experiments and modeling studies indicated that CO 2 enrichment enhanced maize (a C4 plant) yields under drought, but under well-watered conditions yield responses were less consistent (Meng et al, 2016;Twine et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous works that identified temperature as the main factor defining maize performance in the context of global change, with a prevalence of declines in yields (Bassu et al, 2014;Rose et al, 2016;Tao & Zhang, 2011). They are also consistent with recent modeling and meta-analysis reports, which observed a greater sensitivity to rising temperatures in maize than in soybean (Justino et al, 2013;Rose et al, 2016;Zhao et al, 2017). Previous reports from both CO 2 enrichment experiments and modeling studies indicated that CO 2 enrichment enhanced maize (a C4 plant) yields under drought, but under well-watered conditions yield responses were less consistent (Meng et al, 2016;Twine et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, they suggest that the replacement of the forest by urban areas tends to increase the lightning activity in the Amazon region. These results were published in American Journal of Climate Change in December 2013 [1].…”
mentioning
confidence: 87%
“…Nitrogen oxides produced by lightning contribute an important part to the total NO x budget, and sometimes even become the dominant source of NO x ( Labrador et al, 2005 ). It was found that the lightning activity in Manaus city (Brazil) has been increasing throughout the last four decades ( Pinto Jr. et al, 2013 ). The coastal areas of Japan are more likely to be hit by lightning in winter ( Matsui et al, 2020 ).…”
mentioning
confidence: 99%